ChemInform Abstract: Vicinal Difunctionalization of Alkenes: Chlorotrifluoromethylation with CF3SO2Cl by Photoredox Catalysis. Issue 34 (26th August 2014) - Oh, Se Hwan; Malpani, Yashwardhan R.; Ha, Neul; Jung, Young‐Sik; Han, Soo Bong
Abstract The protocol is applied to the late‐stage functionalization of complicated biologically active compounds such as the pesticide rotenone and the insecticide (+)‐nootkatone.